Community voices on climate, peace and security: A social learning approach to programming environmental peacebuilding - Medina, Leonardo; Ensor, Marisa; Schapendonk, Frans; Sieber, Stefan; Pacillo, Grazia; Läderach, Peter R.D.; Hellin, Jon; Bonatti, Michelle (SAGE Publications, 2024)
Approaches to operationalising the linkages between climate, peace and security are increasingly demanded by international organisations. Yet, there is a limited understanding of what effective programming practices that address climate-related security risks entail. Critical voices argue that programme designs often rely on analyses that ignore structural and cultural realities on the ground, leading to technocratic understandings of risks, and prescriptions for action that do not relate to people’s experiences, perceptions and values. Advised by social learning theory, this study developed and evaluated a participatory appraisal method to guide the design of environmental peacebuilding programming strategies meant to address climate-related security risks. The method was evaluated across nine rural locations in Kenya, Senegal and Guatemala, involving 221 participants. Based on a critical evaluation of the method, opportunities and challenges for the use of social learning approaches to advise environmental peacebuilding programming are discussed. Results indicate that appraisal processes of collective reflection can support jointly articulated and context-relevant understandings of climate-related security risks. This shared knowledge can then support local communities in the design of climate adaptation strategies that potentially contribute to sustainable peacebuilding. Settings characterised by low political legitimacy and the unwillingness of conflictive actors to engage in dialogue are identified as barriers for the development of feasible programming strategies.